Implementasi Lagu Modern Sebagai Media Pembelajaran Bahasa Arab bagi Santri Tpq dan Madin Al-Adnani - Rif'atul Husnah; Siti Halimatus Sya'diyah; Maula Nasrifah (Kalam Nusantara Institute, 2025)
Music is one of the learning media that we can use as a learning process to make it more fun and not nbboring, and can provide wider space for knowledge so that it is easier to target and channel it flexibly. Especially for students who still have difficulties in learning Arabic, thus the researcher takesan analysis of the implementation of the song as an Arabic language learning medium to improve the capability of memorizing vocabulary for Madin and Tpq Al-adnani which is located in the village,Tiris east of the river hamlet. Because the main purpose of the research that the researchers have the initiative to discuss as a whole in this study using the asset based community development (ABCD) method. The strategy used in this study is observation of implementation and evaluation. This it can be concluded that the implementation of song media in lelarning Arabic can increase the capability of memorizing Arabic vocabulary